Conservation of neural nicotinic acetylcholine receptors from Drosophila to vertebrate central nervous systems. - Bossy, B (1988)
Nicotinic acetylcholine receptors (nAChR) are found both in vertebrate and insect central nervous systems. We have isolated a Drosophila gene by crosshybridization with a vertebrate probe. Structural conservation of domains of the deduced protein and of intron/exon boundaries indicate that the Drosophila gene encodes an nAChR alpha-like subunit (ALS). That the Drosophila gene product most resembles the neuronal set of vertebrate nAChRs alpha-subunits is also indicated by the failure of an ALS-beta-galactosidase fusion protein to bind alpha-bungarotoxin on blots in contrast to vertebrate endplate alpha-subunit constructions. The ALS encoding gene exceeds 54 kb in length and the transcript has a very long and unusual 5' leader. As we found previously for a gene whose product is also involved in cholinergic synapses, acetylcholinesterase, the leader encodes short open reading frames, which might be involved in translation control. We also note the presence of opa repeats in the gene, as has been found for various Drosophila genes expressed in the nervous system.